Reference values for lead, cadmium, mercury, arsenic, manganese, and tin in blood of the general adult population of Vietnam. - Nguyen, Son Duc; Nguyen, Van Thi; Van Nguyen, Son; Ta, Binh Thi; Phuong Mai, Thao Thi; Vu, Anh Phuong; Khuat, Hai Ngoc; Le, Hai Thanh; Van Pham, Tuan; Van Lo, Tung; Phung, Thao Thi; Pham, Van Thi; et al. (International Journal of Environmental Health Research, 2026)
This study measured and provided reference values for blood concentrations of lead (B-Pb), cadmium (B-Cd), mercury (B-Hg), arsenic (B-As), manganese (B-Mn), and tin (B-Sn) in Vietnamese adults. The study population consisted of 1077 Vietnamese adults of working age (18–60 years) without occupational exposure to heavy metals across all seven regions of Vietnam. The geometric mean, and 95th percentile of B-Pb was 23.52 µg/L, and 50.81 µg/L; of B-Cd was 0.72 µg/L, and 2.62 µg/L; of B-Hg was 4.61 µg/L, and 11.36 µg/L; of B-As was 2.95 µg/L, and 8.25 µg/L; of B-Mn was 15.24 µg/L, and 26.49 µg/L; of B-Sn was 11.29 µg/L, and 34.15 µg/L, respectively. Blood concentrations of Pb, Cd, Hg, As, Mn, and Sn in Vietnamese adults fall within an intermediate to high range compared to other countries. Vietnamese men tend to have significantly higher B-Pb, B-Cd, B-Hg, and B-As than women. B-Pb, B-Cd, and B-Hg in Vietnamese adults increase with age. Male smokers were associated with higher B-Cd, B-Hg, and B-As. Frequent seafood consumption was associated with higher B-Mn, B-Hg, and B-As. Alcohol drinkers were associated with higher B-Pb, B-Cd, B-Hg, and B-As. However, wearing makeup was mostly not associated with blood metal levels in women.